Relatório do estágio curricular supervisionado em medicina veterinária: área de concentração: extensão rural e qualidade do leite - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present report aims to describe the activities followed and performed during the Supervised Curricular Internship in Veterinary Medicine (SCIVM) conducted in the dairy cattle area. This work was under the advisor of Professor Lueli Fernandes Bragança and the supervision of Agronomist Rodrigo Baiotto and Veterinarian Thais Endrigo. The internship was divided into two periods, with the first being conducted at the Serviço de Inteligência em Agronegócio (SIA) company and the second at the Cooperativa Agropecuária e Industrial (COTRIJAL). The internship started on February 22, 2023, and ended on June 28, 2023, totaling 590 hours. During the internship, activities related to consulting in dairy cattle, beef cattle and sheep, team training, milk quality, and calf raising were followed. The topics discussed in this work are focused on milk quality, showing a report of a blitz therapy and the accomplishment of a benchmarking project, demonstrating the evaluated indicators. The SCIVM was highly important to develop and put into practice all the knowledge acquired during my undergraduate studies.
Report on the supervised curricular internship in veterinary medicine: area of concentration: rural extension and milk quality
Keywords: Milk quality; Qualidade do leite; Benchmarking; Dairy cattle; Bovinos de leite; Medicina Veterinária; Grandes animais; CNPQ::CIENCIAS AGRARIAS